A Relentless and Aggressive Proliferation of a Verrucous Lesion - Badam, Raj Kumar; Bontha, Sharath Chandra; Shereen, Arshia; Chowdary, Supraja (Journal of Orofacial Research, 1970)
Proliferative verrucous leukoplakia (PVL) was first described by Hansen in 1985, is a clinical form of oral leukoplakia defined by its progressive features, and potential to develop into cancer. PVL behaves in a more aggressive and relentless manner than the more innocuous white oral lesions that it can resemble clinically. In this paper, we report a case of PVL transforming into squamous cell carcinoma.